Biocompatibility assessment of resin-based cements on vascularized dentin/pulp tissue-engineered analogues. Issue 5 (May 2021) - Hadjichristou, Christina; Papachristou, Eleni; Vereroudakis, Emmanouil; Chatzinikolaidou, Maria; About, Imad; Koidis, Petros; Bakopoulou, Athina
Highlights: The dentin/pulp tissue analogue may be used for cytotoxicity assessment of resinous cements. The composition of the lower compartment (pulp component) affects its stiffness and biological properties. The resinous cements investigated using the dentin/pulp tissue analogue showed variable but mild cytotoxicity. Angiogenesis was not severely affected by the resinous cements under investigation. Abstract: Objectives: A three-dimensional (3D) dentin/pulp tissue analogue, resembling the human natural tissue has been engineered in an in vitro setup, aiming to assess the cytocompatibility of resin-based dental restorative cements. Methods: Stem Cells from Apical Papilla (SCAP) and Human Umbilical Vein Endothelial Cells (HUVEC) were embedded in Collagen-I/Fibrin hydrogels at 1:3 ratio within 24-well plates. Hanging culture inserts were placed over the hydrogels, housing an odontoblast-like cell layer and a human treated-dentin barrier. Shear modulus of the hydrogels at 3.5 and 5 mg/ml was evaluated by dynamic mechanical analysis. Eluates of two resin-based cements, a dual-cure- (Breeze™, Pentron: Cement-1/C1), and a self-adhesive cement (SpeedCEMplus™, Ivoclar-Vivadent: Cement-2/C2) were applied into the dentin/pulp tissue analogue after pre-stimulation with LPS. Cytocompatibility was assessed by MTT assay, live/dead staining and real-time PCR analysis. Results: Both hydrogel concentrations showed similar shear moduli to the natural pulp until day (D) 7, while the 5 mg/ml-hydrogel substantially increased stiffness by D14. Both cements caused no significant toxicity to the dentin/pulp tissue analogue. C1 induced stimulation (p < 0.01) of cell viability (158 ± 3%, 72 h), while pre-stimulation with LPS attenuated this effect. C2 (±LPS) caused minor reduction of viability (15–20%, 24 h) that recovered at 72 h for the LPS+ group. Both cements caused upregulation of VEGF, ANGP-1, and downregulation of the respective receptors VEGFR-2 and Tie-1 . Significance: Both resin-based cements showed good cytocompatibility and triggered angiogenic response within the dentin/pulp tissue analogue, indicating initiation of pulp repair responses to the released xenobiotics.